Analisis Perkembangan Fisik Motorik Anak Melalui Kegiatan Bermain: Studi Kasus Memperingati Hut Ri Ke-78 Di Desa Tamosu - Rindy Regar; Hanis Adira Lubis; Heidi Sahertiah; Dorina Siregar; Rumiah Siregar; Irwansyah Nasution; Rama Wahyudi; Zainul Arifin; Suleha Lubis (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Real work education (KKN) is an education in the form of community service. In this service, students apply the theories they have after studying for several semesters into a real form of community service. In this service, students carry out several activities that develop children's physical motor skills. Physical development is the growth or changes experienced in a person's body which are clearly visible from changes in the shape and size of a person's body. Motor development is controlling the development of body movements through coordinated activity of muscles, nerves and nerve centers. Therefore, a child's physical motoric development is a process that the child goes through regarding the growth and development that occurs in the child. The aim of this research is to find out the extent of children's physical motor development through real work lecture activities.